Cerâmica e pintura corporal indígena: a arte como agente de consolidação do patrimônio imaterial dos Tabajara da Paraíba /PB - Saraiva, Ilson Roberto Moraes (2019)
The research aims to identify the telluric and spiritual relationships in the body paintings of the Tabajara of Paraiba, considering how they are processed and if they manifest the indigenous worldview through ceramic art. To do this, we will identify the historical, cultural and sacred links of this worldview, linking those memories with artistic creation. To base the research, we will use some theorists, such as: Barcellos (2012), Eliade (2007), Cassirer (2012), Hauser (1998), Tolstoy (2016), among others. In this sense, through this research, from a qualitative approach we will use art as a mediator of Tabajara's spirituality. The type of methodology used was Action Research, in which the art used in the production of ceramics will serve as a vehicle to carry out this work, contributing to the strengthening of personal and collective beliefs, indigenous heritage, intangible legacy of these people threatened by other beliefs and cultures. The research tools we used were: journal registration; participant observation and semi-structured interviews; strategies and research instruments that allowed us to be present in daily life; analysis and registration of bodypaint; creation of ceramic pieces printing the visual language of body drawings, observing and relating the manifestations of spirituality with the belief in the spirit of the ancestors and other spiritual entities that can contribute symbolically, adding aesthetic value and identity within the Tabajara indigenous tradition of Paraiba to the pieces produced. The results of this research were the production and creation of Tabajara ceramics centered on the elements of telluric spirituality, strengthening this intangible heritage and providing an appreciation of the indigenous culture and the visibility of this ethnic group.